2018
DOI: 10.1002/aenm.201802116
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Engineering of SnTe: Multi‐Principal‐Element Alloying Leading to Ultralow Lattice Thermal Conductivity and State‐of‐the‐Art Thermoelectric Performance

Abstract: TE material research has attracted intense interest over the past few decades. [1] The TE performance of a material is measured by zT = σS 2 T/κ, where T, σ, S, and κ are the absolute temperature, electrical conductivity, Seebeck coefficient, and total thermal conductivity, respectively. Typically, κ = κ el + κ ph , where the κ el and κ ph are the carrier and lattice thermal conductivity, respectively. Since σ, S, and κ el are adversely interrelated whereas the κ ph is relatively independent of σ, S, and κ el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
203
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(216 citation statements)
references
References 72 publications
7
203
1
5
Order By: Relevance
“…Interestingly, alloying GeSe with Ag or Sb alone didn't stabilize this rhombohedral phase. The alloying-induced new Fermi surface topology and Ge vacancies led to a desired high carrier concentration, close to the optimal one, and a promising ZT ~ 0.86 in GeAg0.2Sb0.2Se1.4 at 710 K. Through alloying SnTe with Ge, Pb, Mn and Te vacancies, Hu et al (2018) reported (i) an extended solubility limit of Mn in (Ge, Pb)-doped SnTe compared to that in pristine SnTe; (ii) a systematic crossover in the carrier scattering mechanism with increasing number of alloying elements, i.e., from electron-phonon scattering to alloy scattering; (iii) the degraded carrier mobility was compensated by increased carrier concentration, heavier effective mass, and band convergence towards a good ZT; and (iv) rich multi-scale microstructures including line defects, strain clusters and dislocation arrays along with point defects led to low lattice thermal conductivity. Fine tuning carrier concentration by Sn excess further boost the peak ZT value to 1.42 at 900 K in (Sn 0.74 Ge 0.2 Pb 0.1 ) 0.75 Mn 0.275 Te.…”
Section: (B) Entropy-engineered Chalcogenide Compoundsmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, alloying GeSe with Ag or Sb alone didn't stabilize this rhombohedral phase. The alloying-induced new Fermi surface topology and Ge vacancies led to a desired high carrier concentration, close to the optimal one, and a promising ZT ~ 0.86 in GeAg0.2Sb0.2Se1.4 at 710 K. Through alloying SnTe with Ge, Pb, Mn and Te vacancies, Hu et al (2018) reported (i) an extended solubility limit of Mn in (Ge, Pb)-doped SnTe compared to that in pristine SnTe; (ii) a systematic crossover in the carrier scattering mechanism with increasing number of alloying elements, i.e., from electron-phonon scattering to alloy scattering; (iii) the degraded carrier mobility was compensated by increased carrier concentration, heavier effective mass, and band convergence towards a good ZT; and (iv) rich multi-scale microstructures including line defects, strain clusters and dislocation arrays along with point defects led to low lattice thermal conductivity. Fine tuning carrier concentration by Sn excess further boost the peak ZT value to 1.42 at 900 K in (Sn 0.74 Ge 0.2 Pb 0.1 ) 0.75 Mn 0.275 Te.…”
Section: (B) Entropy-engineered Chalcogenide Compoundsmentioning
confidence: 97%
“…The references are listed in Table 3. (Hu 2018) distortion. Doping with a trace amount of Ag effectively enhanced the Seebeck coefficient and further reduced the lattice thermal conductivity.…”
Section: (B) Entropy-engineered Chalcogenide Compoundsmentioning
confidence: 99%
“…The configurational entropy (CE) gauges the level of site occupational disorder and thus governs the lattice thermal conductivity L . [3][4][5][6] In diverse research and application regimes of structural and functional materials, there has been a long pressing need for direct visualization of site disorder and quantification of CE in relation to the material's lattice thermal conductvitiy. However, from site disorder and configurational entropy to lattice thermal conductivity, it spans statics and dynamics of crystal lattice as well as the kinetics of thermal transport over orders of magnitude in spatial and temporal domain.…”
Section: Doi: 101002/advs202002051mentioning
confidence: 99%
“…In the NC-Ti 2 NiCoSnSb system (grain size ;12 nm), a secondary phase of TiC is obtained after long ball-milling times, facilitating more Ni 3 Sn 4 formation and leading to higher electrical and thermal conductivities, but undermining the thermoelectric performance [103]. By contrast, Mn-rich nanoscale precipitates (20-30 nm in size) in SnTe-MnTe (medium-entropy) and Sn 0.555 Ge 0.15 Pb 0.075 Mn 0.275 Te (high-entropy) systems promote the formation of nano line-defects, nanoscale strain clusters, and microscale interfaces, which scatter phonons and, therefore, reduce thermal conductivity, leading to excellent thermoelectric properties [106,107]. The results from these studies showing the synergetic effect between nanostructure and lattice distortion are shown in Fig.…”
Section: Thermal Conductivity and Thermoelectric Propertiesmentioning
confidence: 99%